1999
DOI: 10.1016/s0021-9673(99)00524-5
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of adsorption effects in the analysis of water-soluble vitamins in pharmaceutical formulations by capillary electrophoresis

Abstract: A tendency to an increase in migration times was observed when different water-soluble vitamins were analysed repeatedly in pharmaceutical preparations by capillary electrophoresis. In order to better understand the origin of this effect, the influence of the vitamins and the excipients, such as cellulose derivatives, was investigated. These studies indicated that the increase in analyte migration times was most probably due to the adsorption of different kinds of constituents to the capillary wall. Different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Following each run, the capillary was washed for 2 min with buffer containing 25 mm SDS. This SDS content, which is already included in the buffer for the MEKC method, is sufficient for cleaning the capillary between the analyses, so that no further washing steps with acid or alkali are required [4]. The samples were applied to the capillary using the hydrodynamic mode with an overpressure of 0.5 psi for 5 s. The applied voltage was 30 kV and detection was carried out at 214 nm.…”
Section: Optimisation Of the Electrophoretic Methodsmentioning
confidence: 99%
“…Following each run, the capillary was washed for 2 min with buffer containing 25 mm SDS. This SDS content, which is already included in the buffer for the MEKC method, is sufficient for cleaning the capillary between the analyses, so that no further washing steps with acid or alkali are required [4]. The samples were applied to the capillary using the hydrodynamic mode with an overpressure of 0.5 psi for 5 s. The applied voltage was 30 kV and detection was carried out at 214 nm.…”
Section: Optimisation Of the Electrophoretic Methodsmentioning
confidence: 99%
“…Moreover, 10 mM L-cysteine [26,27] was added to all solutions in order to prevent water-soluble vitamins, especially VC, from oxidation in the experimental environment. All solutions were freshly prepared in amber volumetric flasks in the dark every day, and stored in a refrigerator prior to analysis.…”
Section: Reagents and Materialsmentioning
confidence: 99%
“…The amounts of free thiamin in selected commercial tablets determined experimentally are presented in Table 2. It was also observed that tablet samples or matrix components appeared to be adhering to the capillary walls, causing irreproducibility in both migration times and peak areas from run-to-run [30,39]. By reconditioning the capillary as described in Section 2 prior to commercial-tablet sample analyses, an improvement in migration times and peak area precision was obtained (R.S.D.…”
Section: Application To Quantitative Determination Of Thiamin In Commmentioning
confidence: 99%